Hydrogen-Bonded Xanthones as Potential UV Absorbers: The Synthesis of Xanthones from Bio-Renewable Cardanol Utilizing a Ceric Ammonium Sulfate (CAS)-Mediated Oxidation Reaction - Jagot, Fatema; Minnie, Izak; Rahman, Aliyaah; Ntsimango, Songeziwe; Ngwira, Kennedy J.; de Koning, Charles B. (SynOpen, 2022)
The synthesis of hydrogen-bonded xanthones by using biorenewable hydrogenated cardanol (3-pentadecylphenol) is described. Hydrogenated cardanol was initially converted into various hydroxybenzophenones. These benzophenones were converted into xanthones by utilizing an oxidative ceric ammonium sulfate-mediated reaction. A subsequent ruthenium-mediated late-stage oxidation of the xanthones provided hydrogen-bonded xanthones, which displayed good UVA and UVB absorbing properties.
Keywords: cardanols; benzophenones; ceric ammonium sulfate; oxidative addition; xanthones; UV absorbers